Postural control at 4 years in very preterm children compared with term‐born peers. (23rd July 2014) - Lorefice, Lucy E; Galea, Mary P; Clark, Ross A; Doyle, Lex W; Anderson, Peter J; Spittle, Alicia J
<x xml:space="preserve">Abstract</x> Aim To compare postural control at 4 years' corrected age in very preterm children (VPT; <30wks gestational age) with term‐born (>37wks gestational age) comparison participants. Method Ninety VPT children (45 males, 45 females; mean age at assessment 4y 1mo; mean birthweight 1022g; mean gestational age 27.3wks) and 36 term comparison participants (17 males, 19 females; mean age at assessment 4y; mean birthweight 3507g; mean gestational age 39.4wks) were assessed for postural stability with a portable force plate, the Wii Balance Board. Tasks included static two‐limbed standing with eyes open, eyes closed, eyes open on a foam mat, eyes closed on a foam mat, a cognitive dual task, and single leg standing on each limb. The cognitive dual task involved showing the participants a series of pictures that appeared on screen at 2‐second intervals. Impaired postural control was defined as increased postural sway measured by centre of pressure path‐length velocity. Functional performance was assessed during dynamic jumping and hopping tasks using the outcome measure flight time, with shorter time indicating worse performance. Results VPT children had impaired static and dynamic balance, with increased postural sway under all conditions, and reduced flight times compared with children born at term. When results were adjusted for body weight, the only group differences in postural control were in the cognitive dual task (cm/s; mean difference 0.6; 95% confidence interval [CI] 0.02, 1.2; p=0.04) and flight times (ms; jumping; mean difference −26.0; 95% CI −47.1, −5.0; p=0.02; left leg hopping; mean difference −30.1; 95% CI −48.5, −11.8; p=0.002). Interpretation VPT children demonstrated reduced postural control at 4 years of age compared with term‐born children when presented with a cognitive dual task. They also performed worse during jumping and hopping tasks.